Protein from paraffin - Artiaga, Josefina V.; Moreno, Melba T.; Sotto, Rolando M. (Quezon City College of Engineering, 1970)
Plant: Protein from Paraffin Plant -- Location: Diliman, Quezon City -- Capacity: Raw materials 761,400 lbs/yr, Products 600,000 lbs/yr -- Fixed capital investment: 7,276,876 -- Working capital: 808,544 -- Operating cost at maximum production: 13,690,355 -- Annual sales at maximum production: 22,817,233 -- Break-even point: 228,000 lbs/yr -- Annual rate of return on investment: 50 -- Pay-out time: 1.68 years
Typescript.
Plant design.
Keywords: Factories -- Design and construction; Alkanes